Static Balance Reliability Test with One Leg Stance Test in Knee Osteoarthritis Patients - Dwi Rosella Komalasari; Shafira Rizky Nur Khairunnisa (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Introduction: Osteoarthritis (OA) is the most common joint inflammation that often occurs in the knee region and its prevalence increases with age. The prevalence of knee OA is the highest compared to other regions. Static balance is one of the problems in OA patients which is evaluated by the One leg stance test, but the reliability of this measuring instrument for patients with knee OA has not been reported in Indonesia. Research objective: To determine the reliability of the intra rater and inter rater one leg stance test as a measure of static balance in patients with knee osteoarthritis. Materials and methods: The research method used was an observational study with a methodological research approach. There were 58 respondents who signed informed consent and were involved in this study. Results/findings: Intra rater reliability showed a very high internal consistency in both right and left eye open positions (?>0.9) with ICC=0.8-0.9. Whereas OLS in closed eyes shows moderate to low internal consistency and moderate ICC. The results of the inter-rater reliability analysis showed very high internal consistency and ICC for the right and left leg open eyes. Whereas in closed eyes it has internal consistency and moderate to high ICC for the right and left. Conclusion: The ability to maintain static balance in the closed eye position is something that is not easy for patients with knee OA to do, possibly due to pain and also reduced function in the elderly, this is indicated by the low consistency value for OLS in the closed eye position.